The influence of media exposure in the form of content on the instagram account @infojajansolo on visit interest - Irliana, Jauzaa Salwa; Saputro, Edy Purwo; Setyawan, Sidiq; Apriliani, Riski (Trigin Publisher, 2025)
Media exposure is one of the causes of changes in behavior, perspectives, desires, and preference of each individual affected. So, form the resulting impact this research aim to find out how media exposure in the dorm of content on the Instagram account @infojajansolo influences visiting interest. The theory used in this research is S-O-R, which is the theory of understanding the impact of attachment that arises due to a drive. Sample collection uses probability techniques where not all prpolations have the same opportunity. The data in this study were collected through an online survey using a questionnaire distributed to 100 respondents, followers of the Instagram account @infojajansolo, using purposive sampling technique. The questionnaire was designed to measure the influence of Instagram content on visit intentions. The results of the study showed that Instagram content had an influence of 45.7% on visit intentions, while 54.3% was influenced by other factors. These findings indicate that social media, particularly Instagram, is effective in influencing the audience's interest, but other external factors should also be considered in marketing strategies.